Laparoscopic lateral duodenojejunostomy for pediatric superior mesenteric artery compression syndrome: a cohort retrospective study - Jingfeng Tang; Mengxin Zhang; Ying Zhou; Guoqing Cao; Shuai Li; Xi Zhang; Shaotao Tang (BMC Surgery, 2023)
Abstract Purpose There are only a few case reports of laparoscopic lateral duodenojejunostomy (LLDJ) in children with Wilkie’s syndrome, also known as superior mesenteric artery compression syndrome (SMAS). We aimed to describe our laparoscopic technique and evaluate its outcomes for SMAS in children. Methods From January 2013 to May 2021, SMAS children who received LLDJ were included. The procedure was carried out utilizing the four-trocar technique. The elevation of the transverse colon allows good exposure of the dilated and bulging second and third sections of the duodenum. Using a linear stapler, we established a lateral anastomosis connecting the proximal jejunum with the third part of the duodenum. Following that, a running suture was used to intracorporeally close the common enterotomy. Clinical data on patients was collected for analysis. The demographics, diagnostic findings, and postoperative outcomes were analyzed retrospectively. Results We retrospectively analyzed 9 SMAS patients (6 females and 3 males) who underwent LLDJ, aged between 7 and 17 years old. The mean operative time was 118.4 ± 16.5 min and the mean estimated blood loss was 5.6 ± 1.4 ml. There were no conversion, intraoperative complications or immediate postoperative complications. The mean postoperative hospital stay was 6.8 ± 1.9 days and the mean follow-up time was 5.4 ± 3.0 years. During follow-up, seven patients (77.8%) experienced complete recovery of symptoms prior to surgery. One patient (11.1%) still had mild vomiting, which resolved with medication. Another patient (11.1%) developed psychological-induced nausea, which significantly improved after treatment with education, training and diet management. Conclusions LLDJ represents a feasible and safe treatment option for SMAS in well-selected children. Further evaluation with more cases and case-control studies is required for the real benefits.